Trends of potentially illegal deforestation over protected areas of Rio das Velhas basin, Brazil - de Oliveira, Amanda Ribeiro (2023)
Despite the promise to increase control and fight against deforestation, the new Brazilian Forest Code (BFC) allowed more flexible dimensioning and land use rules in areas of private rural properties intended for native vegetation protection, namely the Legal Reserve (LR) and Areas of Permanent Preservation (APP). Following a decade of BFC implementation, the promise was somewhat flawed, while oversight and monitoring of private rural properties were not as expected. Considering this worrying scenario, the objective of this study was to quantify and map the forest balance of private rural properties listed in the Environmental Rural Registry of Rio das Velhas hydrographic basin (Minas Gerais, 2002), to assess compliance with the BCF and detect potentially illegal deforestation. The total deforested area in 6216 (28.7%) registered private rural properties reached approximately 119,800 ha after 2008, 61,500 ha of which were suppressed without surplus forest of LR. Besides, nearly half of the private rural properties presented forest deficits in the APPs. In a vast majority of cases, the deforestation was potentially illegal, but only a small number of private rural property owners was made responsible for that. The deforested areas were concentrated in small sectors within the rural properties, which would facilitate the control of illegal native vegetation suppression if oversight and law enforcement had been effective. Our results are an alert and a subside to public institutions and rural property owners while developing and executing plans, programs, and projects focused on environmental regularization of rural properties, with the ultimate goal of preventing further land degradation in the basin.